Predictors of advanced disease and late presentation in new HIV diagnoses reported to the surveillance system in Spain - Jesús Oliva; Mercedes Díez; Silvia Galindo; Carlos Cevallos; Ana Izquierdo; Javier Cereijo; Arantxa Arrillaga; Antonio Nicolau; Ana Fernández; Mara Álvarez; Jesús Castilla; Eva Martínez; et al. (Gaceta Sanitaria, 2014)
Objective: To present surveillance data on advanced disease (AD) and late presentation (LP) of HIV in Spain and their determinants. Methods: We included all new HIV diagnoses notified by the autonomous regions that consistently reported such cases throughout the period 2007–2011. Coverage was 54% of the total Spanish population. Data sources consisted of clinicians, laboratories and medical records. AD was defined as the presence of a CD4 cell count <200 cells/μL in the first test after HIV diagnosis, while LP was defined as the presence of a CD4 cell count <350 cells/μL after HIV diagnosis. Odds ratios and their 95% confidence intervals (OR, 95% CI) were used as the measure of association. Logistic regressions were fit to identify predictors of AD and LP. Results: A total of 13,021 new HIV diagnoses were included. Among these, data on the outcome variable were available in 87.7%. The median CD4 count at presentation was 363 (interquartile range, 161–565). Overall, 3356 (29.4%) patients met the definition of AD and 5494 (48.1%) were classified as LP. Both AD and LP increased with age and were associated with male sex and infection through drug use or heterosexual contact. All immigrants except western Europeans were more prone to AD and LP. Multivariate models disaggregated by sex showed that the effect of age and region of origin was weaker in women than in men. Conclusions: Despite universal health care coverage in Spain, men, immigrants and people infected through drug use or heterosexual contact seem to be experiencing difficulties in gaining timely access to HIV care.